Plasma concentrations of direct oral anticoagulants in patients with nonvalvular atrial fibrillation and different degrees of obesity - Menichelli, Danilo; Pannunzio, Arianna; Baldacci, Erminia; Cammisotto, Vittoria; Castellani, Valentina; Mormile, Rosaria; Palumbo, Ilaria Maria; Chistolini, Antonio; Violi, Francesco; Harenberg, Job; Pastori, Daniele; Pignatelli, Pasquale (Clinical pharmacokinetics, 2025)
Background: Atrial fibrillation (AF) has multiple cardio-metabolic comorbidities, including obesity. The use of direct oral anticoagulants (DOACs) in patients with AF and obesity is still uncertain owing to the concern of possible ineffective DOAC plasma concentration. We evaluated the peak and trough plasma concentrations of DOACs in AF patients with different degrees of obesity. Methods: Observational single-center study including patients with obesity and AF, between April 2022 and April 2024. Obesity was defined as body mass index (BMI) ≥ 30.0 kg/m2. The 2-hour peak and trough DOAC plasma concentrations were assessed. Intake of DOAC was verified on site. Multivariable logistic regression analysis was used to assess the odds ratio (OR) and 95% confidence interval (95% CI) of factors associated with below-range trough concentration (BRTC) and below-range peak concentration (BRPC). Results: In total, 160 patients (33.8% women) with a mean age of 73.2 ± 9.1 years were included. The median BMI was 32.3 kg/m2. DOACs prescribed were apixaban (46.8%), rivaroxaban (21.8%), dabigatran (16.4%), and edoxaban (15.0%); 18.1% and 14.4% had BRTC and BRPC concentrations, respectively. Patients with BRTC were more frequently treated with edoxaban and dabigatran and had a higher BMI. On multivariable logistic regression analysis, dabigatran [hazard ratio (HR) 3.039, 95% CI 1.155–7.999, p = 0.024) and BMI ≥ II class (OR 2.625, 95% CI 1.087–6.335, p = 0.032] were associated with BRTC. Dabigatran (OR 4.296, 95% CI 1.523–12.120, p = 0.006) and apixaban (OR 0.277, 95% CI 0.096–0.802, p = 0.018) were directly and inversely associated with BRPC, respectively. Conclusions: A nonnegligible proportion of patients with obesity and AF have below-range plasma concentrations of DOACs. Assessment of DOAC plasma concentration in obesity class ≥ II may be useful in these patients.